MANAGEMENT AND FUNDING FOR QUALITY ASSURANCE IN THE CURRICULA OF HIGHER EDUCATION IN NIGERIA - Alade, Ibiwumi A (International Journal of Educational Development in Africa, 2015)
The pursuit of quality in education has become a worldwide phenomenon. This stems from the astronomical demand for higher education, as well as the rising integration of relevant emerging educational reforms in the Nigerian curricula. Despite the efforts at promoting best practices in ensuring quality of achievement and learning outcomes, the management and funding of higher education have been criticised for being regressive in recent years. On this premise, this article examines management and funding for quality assurance in the curricula of higher education in Nigeria. The article appraises the concerted actions of management and quality control agencies that are involved in the transformation of the higher education landscape in Nigeria. Some reform measures, which have gained entrance into Nigerian higher education, are also enunciated with a critique of the dire financial situation of higher education in Nigeria, as evidenced by some financial reports from appropriate sources. Similarly, the issue of quality echoed frequently in Nigerian higher education is critically examined. Some of the submissions in the end include the need for the installation of a sustainable culture of quality reforms management and use of adequate financial sharing formula with a view to proving curricula output of higher education in Nigeria.